Perbandingan algoritma kriptografi simon dan vigenere dalam mengamankan citra digital - Yulia Fatma; Reny Medikawati T; Yoze Rizki; Bagas Tri Ramadana (Computer Science and Information Technology, 2023)
Digital image files or images are sometimes a valuable asset. Digital images that are private and confidential are very vulnerable to interception by other parties, especially if the image is distributed via the internet. To increase the security of digital images so that their confidentiality can be maintained, a special technique is needed to protect digital image messages, namely with cryptographic techniques. This study aims to determine the performance of the SIMON algorithm for digital image security. SIMON algorithm performance results are compared with the vigenere cipher algorithm in terms of time and image file size produced. In this study used base64 encode for the encryption process and base64 decode for the decryption process. The performance of the SIMON algorithm in securing digital images results in an average encryption time of 969 ms and an average decryption time of 1537 ms. The SIMON algorithm requires a longer time for the encryption and decryption process when compared to the Vigenere algorithm. The cipher image encrypted by the SIMON algorithm has a size larger than the original file by 36%. However, when compared to the cipher image encrypted by the Vigenere algorithm, there is no significant difference. The UACI value obtained from the SIMON algorithm cipher image obtained an average yield of 18.94%. Based on the theory of differential analysis, it can be said that this value is still vulnerable to differential attack. This is based on the UACI value which has not met the minimum threshold value of 33%.